Widespread Inter- and Intra-Domain Horizontal Gene Transfer of d-Amino Acid Metabolism Enzymes in Eukaryotes - Naranjo-Ortíz, Miguel A.; Brock, Matthias; Brunke, Sascha; Hube, Bernhard; Marcet-Houben, Marina; Gabaldón, Toni (Frontiers in Microbiology, 2016)
Analysis of the growing number of available fully-sequenced genomes has shown that Horizontal Gene Transfer (HGT) in eukaryotes is more common than previously thought. It has been proposed that certain gene classes may be more prone to HGT than others, but we still have a very poor understanding of what selective forces drive eukaryotic HGT. Recent work uncovered that d-amino acid racemases have been commonly transferred from bacteria to fungi, but their role in the receiving organisms is currently unknown. Here, we set out to assess whether d-amino acid racemases are commonly transferred to and between eukaryotic groups. For this we performed a global survey that used a novel automated phylogeny-based HGT-detection algorithm (Abaccus). Our results revealed that at least 7.0% of the total eukaryotic racemase repertoire is the result of inter- or intra-domain HGT. These transfers are significantly enriched in plant-associated fungi. For this group we hypothesize a possible role for the acquired racemases allowing to exploit minoritary nitrogen sources in nitrogen-poor environments. Finally, we performed experiments on a transferred aspartate-glutamate racemase in the fungal human pathogen Candida glabrata, which however revealed no obvious biological role.